Pengembangan modul bimbingan dan konseling untuk pengelolaan stres akademik siswa - Mufadhal Barseli; Ifdil Ifdil; Mudjiran Mudjiran; Z. Mawardi Efendi; Nilma Zola (Jurnal Konseling dan Pendidikan, 2020)
The purpose of this study was to reveal whether the guidance and counseling module for the management of academic stress of students eligible materially and appearance, and to describe the usefulness level guidance and counseling module for the management of a student's academic stress by counselor. The method used in this research is model ADDIE. Research carried out by testing product research and FGD. The data were analyzed using descriptive and inferential analysis. The results showed that the guidance and counseling module for the management of a student's academic stress can be used as a media in the service guidance and counseling in school. Thus, prototype of guidance and counseling module for the management of a student's academic stress can be used by the counselor to help a student in academic stress anticipate in the learning process.